Going beyond mere rhetoric of school readmission for adolescent mothers: a case study in remote villages in Kenya with a high prevalence of early pregnancy - Opiyo, Rose Atieno; Elizabeth, Nanyama M. (Frontiers in Education, 2025)
Adolescent motherhood is widespread and can have far reaching impacts on the education and the health of girls. WHO has called for research on the interventions to promote school re-entry, retention and completion by adolescent mothers that are being implemented in diverse settings. This study answers this call in the context of the Kenyan government's current guidelines to support adolescent mothers' return to school. It documents diverse stakeholders' beliefs about the interventions that are effective in supporting continued schooling among adolescent mothers. Rich qualitative data were collected through semistructured interviews with 32 respondents in a rural area of Kenya with a high prevalence of teenage pregnancy. A thematic analysis indicated that most, but not all school principals supported the government's 100% transition and re-entry policies. Although some principals were proactive in sensitizing students' parents/guardians about this policy, one actively resisted it. Adolescent mothers valued schools' attempts to support their parenting, provide childcare and menstrual hygiene facilities, and to promote their social acceptance by other students. The parents of adolescent mothers expressed diverse views ranging from conservative perspectives that favoured early forced marriage to preserve the family's social standing to liberal perspectives that promoted open communication about sexuality. The additional financial challenges that adolescent mothers and their families faced during the COVID-19 pandemic were identified as a special impediment to girls' continued education. In Kenya, the development and promulgation of a series of school re-entry policies has not changed the behaviour of all key stakeholders or provided the material and emotional support necessary to allow all girls to fully benefit from these policies. These findings may stimulate more innovative interventions and actions promoting school access, retention and completion of adolescent mothers in low-and middle-income countries.